IMPLEMENTATION OF E-GOVERMENT IN THE POPULATION AND CIVIL REGISTRATION OFFICE OF TULUNGAGUNG DISTRICT (INTERNATIONAL SEMINAR, 2023)
The aim of this research is to determine the application of e-government, in thiscase the PANDU CAKTI application at the Tulungagung Regency Population and CivilRegistry Service. The research method used by researchers is qualitative research. Theresearch design used is an analytical description research type, namely research that is usedto describe in detail the research object and analyze social phenomena, in this case theapplication of e-government at the Population and Civil Registry Service of TulungagungRegency. Based on the results of research conducted by the author, in implementing EGovernment in the Tulungagung Regency Population and Civil Registry Service, severalresults were produced, including that the support provided by the Tulungagung RegencyPopulation and Civil Registry Service regarding the implementation of E-Government hasbeen said to be very good. , in this way the support provided includes placing severalservices in villages far from the Tulungagung district Population and Civil Registry Office,conducting socialization about E-Government and providing facilities that support operatorperformance, Availability of resources to implement E-Government at the PopulationService and The civil record of Tulungagung Regency, both in terms of human resourcesand financial resources, is quite good.